Antibiotic susceptibility pattern of bacterial isolates from soft tissues infections among patients visiting a tertiary care centre - Shrestha, Kewal; Yadav, Kumari Ragani; Singh, Ganesh Kumar; Kumar, Prabhat (Journal of Kathmandu Medical College, 2023)
Background: Pus is a thick, white to yellow fluid that consists of dead leucocytes, cellular debris, necrotic tissues, and bacteria characteristic of pyogenic infections that may be exogenous or endogenous. The resistant pathogens isolated from wound infections have become a global challenge and a grave threat to the public health worldwide. Objectives: To characterise the bacterial isolates from clinical specimens of pyogenic wound infections and to determine the antibiotic susceptibility test. Methods: A hospital-based, descriptive, cross-sectional study was carried out after ethical clearance in the department of microbiology, Nobel Medical College from 2021 May to 2022 January. Various clinical specimens were obtained by convenience sampling. Identification and antibiotic sensitivity test were done as per the standard microbiological procedures. Data were analysed by SPSS v.20. Results: Out of 1704 sample collected, 901 (52.8%) showed growth in which 893 (52.4%) showed monomicrobial growth and 8 (0.46%) showed mixed growth. Among the samples, females outnumbered males (F: M-1.4:1) and majority of infection were observed in age group between 21-30 years. Most of the isolates were Gram-negative bacteria (462, 50.8%) which were mostly sensitive to amikacin. The most predominant organism was Staphylococcus aureus (427, 47%) which was 100% sensitive to vancomycin and highly resistant to ampicillin (341, 79.8%). Conclusion: The dryness in the pipeline of new antibiotic and emergence of multidrug resistant strains have pointed the current need towards active microbial surveillance in all clinical settings and prudent use of antibiotics.